Nicotine, Auditory Sensory Memory, and sustained Attention in a Human Ketamine Model of Schizophrenia: Moderating Influence of a Hallucinatory Trait - Knott, Verner; Shah, Dhrasti; Millar, Anne; McIntosh, Judy; Fisher, Derek; Villeneuve, Crystal; Ilivitsky, Vadim (Frontiers in Pharmacology, 2012)
Background: The procognitive actions of the nicotinic acetylcholine receptor (nAChR) agonist nicotine are believed, in part, to motivate the excessive cigarette smoking in schizophrenia, a disorder associated with deficits in multiple cognitive domains, including low-level auditory sensory processes and higher-order attention-dependent operations. Objectives: As N-methyl-d-aspartate receptor (NMDAR) hypofunction has been shown to contribute to these cognitive impairments, the primary aims of this healthy volunteer study were to: (a) to shed light on the separate and interactive roles of nAChR and NMDAR systems in the modulation of auditory sensory memory (and sustained attention), as indexed by the auditory event-related brain potential – mismatch negativity (MMN), and (b) to examine how these effects are moderated by a predisposition to auditory hallucinations/delusions (HD). Methods: In a randomized, double-blind, placebo-controlled design involving a low intravenous dose of ketamine (0.04 mg/kg) and a 4 mg dose of nicotine gum, MMN, and performance on a rapid visual information processing (RVIP) task of sustained attention were examined in 24 healthy controls psychometrically stratified as being lower (L-HD, n = 12) or higher (H-HD) for HD propensity. Results: Ketamine significantly slowed MMN, and reduced MMN in H-HD, with amplitude attenuation being blocked by the co-administration of nicotine. Nicotine significantly enhanced response speed [reaction time (RT)] and accuracy (increased % hits and d′ and reduced false alarms) on the RVIP, with improved performance accuracy being prevented when nicotine was administered with ketamine. Both % hits and d′, as well as RT were poorer in H-HD (vs. L-HD) and while hit rate and d′ was increased by nicotine in H-HD, RT was slowed by ketamine in L-HD. Conclusions: Nicotine alleviated ketamine-induced sensory memory impairment and improved attention, particularly in individuals prone to HD.